Nausea and Vomiting in Head-Neck Surgery - Yaşar, M. Akif; Avcı, Levent (Fırat University, 2002)
Aim: In our study, we planned to investigate the effects of head-neck and extremity surgery on postoperative nausea and vomiting (PONV). Material and Methods: Ninety ASA I-II class patients undergoing head-neck and extremity surgery were included to our study. Anaesthesia was induced by thiopental 5mg/kg, fentanyl 150 mg and vecuronium 0.01 mg/kg. Patients divided into two groups; in group I, undergoing head neck surgery (n=62), in group II, extremity surgery (n=58). The demographic data of patients, type of surgery, duration of surgery were recorded, and observed for the incidence of PONV for 24 hours period. Results: During first 24 hours, PONV were observed at 15 and 4 patients in group I and II, respectively (p

Amaç: Çalışmamızı baş boyun ve ekstremite cerrahisinin postoperatif bulantı kusmaya (POBK) etkilerini araştırmak için planladık. Gereç ve Yöntem: ASA I-II grubu baş boyun ve ekstermite cerrahisi geçirecek 120 hasta çalışmaya alındılar. Anestezi indüksiyonunda 5 mg/kg tiopental, 150 mg fentanil ve 0.01 mg/kg vekuronyum kullanıldı. Hastalar; baş boyun cerrahisi (grup I, n=62) ve ekstremite cerrahisi (grup II, n=58) hasta olmak üzere iki gruba ayrıldı. Hastaların demografik verileri, cerrahinin tipi cerrahinin süresi kaydedildi ve POBK insidansı 24 saat gözlendi. Bulgular: İlk 24 saatte POBK sıklığı grup I'de 15 ve grup II'de 4 hastada gözlendi (p
BAŞ BOYUN CERRAHİSİNDE BULANTI KUSMA